2003
DOI: 10.1002/ajpa.10305
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutritional status of Khasi boys in Northeast India relating to exogamous marriages and socioeconomic classes

Abstract: The Khasis are one of the matrilineal tribes of Meghalaya in Northeast India. They belong to the Indo-Mongoloid racial stock, and speak the Monkhmer language of the Austro-Asiatic group. They have their own traditional religion (Niam Khasi), but about 65% of them have converted to Christianity. A few Khasi members have also embraced Islam through matrimonial relationship with immigrant Muslim males. The present study was based on a cross-sectional sample of 1,351 urban Khasi boys aged 3-18 years belonging to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…Subject to further studies, excess CED among adolescent boys in both the Khasi subgroups might not be indicative of nutritional discrimination against males, although daughter preference may arise as for the question of family lineage. In addition, the arrival of Christianity in the Khasi hills of Meghalaya is believed to have brought about a tremendous change in the Khasi society (Khongsdier & Mukherjee, 2003a). The present study, however, failed to obtain a significant relationship between religion and CED in both the Khasi subgroups.…”
Section: Role Of Cultural Diversitycontrasting
confidence: 85%
See 2 more Smart Citations
“…Subject to further studies, excess CED among adolescent boys in both the Khasi subgroups might not be indicative of nutritional discrimination against males, although daughter preference may arise as for the question of family lineage. In addition, the arrival of Christianity in the Khasi hills of Meghalaya is believed to have brought about a tremendous change in the Khasi society (Khongsdier & Mukherjee, 2003a). The present study, however, failed to obtain a significant relationship between religion and CED in both the Khasi subgroups.…”
Section: Role Of Cultural Diversitycontrasting
confidence: 85%
“…Information on household monthly income was crosschecked by taking into consideration the other aspects of economic conditions such as housing conditions including ownership of a house, livestock, type of cooking fuel, ownership of agricultural land, occupation and monthly expenditure. The sample households were then arbitrarily divided into lower and higher income groups, considering the mean À 4s.d./ON of the per capita monthly income as the cutoff point (Khongsdier, 2002;Khongsdier & Mukherjee, 2003a). Individual religious affiliation was based on the information whether an individual belonged to Christianity or traditional religion (indigenous religion).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from Meghalaya showed that the prevalence of underweight, stunting and wasting was 60.0%, 29.0% and 6.0% respectively in Khasi children aged 3-18 years. [36] A study conducted in the Purulia district of West Bengal found that the prevalence of underweight, stunting and wasting in Santal children was 33.7%, 17.9% and 29.4%, respectively. [18] Bisai et al [5] recently reported that the prevalence of underweight, stunting and wasting was 33.9%, 26.1% and 19.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Northeast India, the prevalence of undernutrition (53.9%) is found among school-aged children in Assam [18]. Another study among Khasi boys aged 3-18 years of Meghalaya shows the prevalence of underweight at 60.0 percent [19]. e prevalence of overweight among Mishing boys and girls is found to be 1.95 percent and 1.96 percent, respectively [20].…”
Section: Introductionmentioning
confidence: 97%